DIAGNOSTICS AND PLANNING OF ORTHODONTIC TREATMENT OF PATIENTS WITH DENTAL ARCH NARROWING USING 3D TECHNOLOGIES - Yu.M. Voliak; Z.R. Ozhohan (Український стоматологічний альманах, 2018)
According to some authors, dentofacial abnormalities occur in 33.7% - 74.0% on average manifesting in maxilla narrowing and teeth crowding in cases of lack of spaces in the dental row and are characterized by decrease in longitudinal length of dentition.